Global Digital Data Governance Polycentric Perspectives - Aguerre, Carolina; Campbell-Verduyn, Malcolm; Scholte, Jan Aart (Routledge Global Cooperation Series, 2024)
This book provides a nuanced exploration of contemporary digital data governance, highlighting the importance of cooperation across sectors and disciplines in order to adapt to a rapidly evolving technological landscape. Most of the theory around global digital data governance remains scattered and focused on specific actors, norms, processes, or disciplinary approaches. This book argues for a polycentric approach, allowing readers to consider the issue across multiple disciplines and scales. Polycentrism, this book argues, provides a set of lenses that tie together the variety of actors, issues, and processes intertwined in digital data governance at subnational, national, regional, and global levels. Firstly, this approach uncovers the complex array of power centers and connections in digital data governance. Secondly, polycentric perspectives bridge disciplinary divides, challenging assumptions and drawing together a growing range of insights about the complexities of digital data governance. Bringing together a wide range of case studies, this book draws out key insights and policy recommendations for how digital data governance occurs and how it might occur differently. Written by an international and interdisciplinary team, this book will be of interest to students and scholars in the field of development studies, political science, international relations, global studies, science and technology studies, sociology, and media and communication studies.